2017
DOI: 10.1111/pcn.12543
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against voltage‐gated potassium channel and glutamic acid decarboxylase in psychosis: A systematic review, meta‐analysis, and case series

Abstract: Antibodies to the voltage-gated potassium channel (VGKC) complex and glutamic acid decarboxylase (GAD) have been reported in some cases of psychosis. We conducted the first systematic review and meta-analysis to investigate their prevalence in people with psychosis and report a case series of VGKC-complex antibodies in refractory psychosis. Only five studies presenting prevalence rates of VGKC seropositivity in psychosis were identified, in addition to our case series, with an overall prevalence of 1.5% (25/17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Lately, there has been interest in patients with psychosis who may have serum antibodies to neuronal antigens [12][13][14]. Furthermore, a recent meta-analysis suggests that anti-GAD antibodies are more common in patients with psychosis than in controls [15]. Interestingly, our study showed the contrary: we found a lower prevalence of psychiatric symptoms in anti-GAD positive patients compared with anti-GAD negative patients.…”
Section: Discussioncontrasting
confidence: 82%
“…Lately, there has been interest in patients with psychosis who may have serum antibodies to neuronal antigens [12][13][14]. Furthermore, a recent meta-analysis suggests that anti-GAD antibodies are more common in patients with psychosis than in controls [15]. Interestingly, our study showed the contrary: we found a lower prevalence of psychiatric symptoms in anti-GAD positive patients compared with anti-GAD negative patients.…”
Section: Discussioncontrasting
confidence: 82%
“…In presumed psychosis and schizophrenia spectrum disorders associated with psychotic symptoms, various antibodies in serum have been reported: α7nAChR (alpha 7 subunit nicotinergic acethylcholine receptor), CV2/CRMP5-, CRHM1 (cholinergic receptor, muscarinergic 1), DPPX, GABAAR, HuD, LGI1, NMDAR, Recoverin, Synapsin and VGKC ( Chandley et al., 2009 ; Dahm et al., 2014 ; Endres et al., 2015 ; Grain et al., 2017 ; Lennox et al., 2017 ; Mantere et al., 2018 ; Oviedo-Salcedo et al., 2018 ; Sæther et al., 2017 , 2019 ; Shiwaku et al., 2020 , Steiner et al., 2013 ; Tanaka et al., 2003 ; Tong et al., 2019 ; Yarlagadda, 2008 ; Zandi et al., 2011 ; Zandian et al., 2017 ) ( Table 1 ). A much smaller group of CSF antibodies (CV2/CRMP5, DPPX, Hu, NMDAR, VGKC and Yo-antibodies, Table 1 ) is known to be associated with psychotic disorders ( Endres et al., 2015 ) suggesting a high probability of this disorder’s CNS autoimmune origin ( Table 1 , Table 2 ).…”
Section: Psychiatric Symptoms and Syndromes Associated With Autoantibodiesmentioning
confidence: 99%
“…Low levels of positive anti-GAD56 antibodies are found in diabetes mellitus, however, in our cohort, one patient had increased concentrations of anti-GAD65 antibodies in RIA without diabetes mellitus. Increased levels of anti-GAD65 antibodies are found more frequently in patients with psychosis than in control groups [31] and can be associated with limbic encephalitis in a subgroup of the patients with high titers; however, their pathophysiological role is not yet clear [32]. The rheumatic screening showed CRP increases in 17% of the patients.…”
Section: Blood Analysesmentioning
confidence: 99%